2020
DOI: 10.13189/ujer.2020.080953
|View full text |Cite
|
Sign up to set email alerts
|

Reading Literacy in Moslem-Majority Countries: Evidence from PISA

Abstract: Most Moslem-Majority countries nowadays are still facing a low reading literacy rate of their population, even though the first verse revealed in the Quran speaks of the importance of reading in human life. This paper is aimed at portraying reading literacy in the Moslem world and identifying factors influencing this literacy attainment based on PISA studies. The descriptive-comparative analysis is used to depict the students' reading performance of ten Moslem-Majority countries participating in PISA. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Among them are the Muslim majority, i.e., Bangladesh, Egypt, Indonesia, and Pakistan (UNESCO Institute for Statistics, 2008). Using data from Programme for International Student Assessment (PISA) 2009, Yusuf (2020) showed that overall average scores of all Muslim majority countries in reading are lower than OECD's average (only 395.7). Students from Turkey have the highest score (464), followed by Dubai (UAE, 459), Jordan (405), Tunisia (404), and Indonesia (402).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them are the Muslim majority, i.e., Bangladesh, Egypt, Indonesia, and Pakistan (UNESCO Institute for Statistics, 2008). Using data from Programme for International Student Assessment (PISA) 2009, Yusuf (2020) showed that overall average scores of all Muslim majority countries in reading are lower than OECD's average (only 395.7). Students from Turkey have the highest score (464), followed by Dubai (UAE, 459), Jordan (405), Tunisia (404), and Indonesia (402).…”
Section: Introductionmentioning
confidence: 99%
“…Only 0.07% of Muslim students can reach this level of thinking skills. Most students cannot master fundamental knowledge and skills for the 21st century (Yusuf, 2020), making it harder for young Muslims to compete and improve their well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation